Posisi Pasien terhadap Tekanan Vena Sentral - Armi Armi; Mila Sartika (Jurnal Keperawatan Silampari, 2021)
This study aims to identify an increase in central venous pressure in patients given lateral or prone position interventions and to identify the rise in central venous pressure in patients given semi-fowler position intervention in the intensive care unit. This study uses a Quasi-Experimental method with a Case-Control design. The results obtained are the p-value of 0.000, meaning that the research significantly affects the positioning of the central venous pressure (CVP). In conclusion, there was an increase in the average CVP value before and after the passive position intervention was -1,967 cmH2O; on the other hand, there was a decrease in the average CVP value before and after the semi fowler position intervention was 1,867 cmH2O. Keywords: Supine and Semi Fowler Position, Central Venous Pressure